Systemic Inflammatory Indicators as Prognosticators in Glioblastoma Patients: A Comprehensive Meta-Analysis - Yang, Chao; Wen, Hong-Bin; Zhao, Yu-Hang; Huang, Wen-Hong; Wang, Ze-Fen; Li, Zhi-Qiang (Frontiers in Neurology, 2020)
Background: Inflammation plays an important role in tumorigenesis. Previous studies have reported the prognostic value of several peripheral inflammatory markers in glioma patients, including the neutrophil-to-lymphocyte ratio (NLR). However, it still remains unclear whether inflammatory markers can independently predict the prognosis of glioblastoma (GBM) patients. The present study aims to explore the prognostic value of systemic inflammatory markers, including neutrophils, lymphocytes, platelets, the NLR, and the platelet-to-lymphocyte ratio (PLR), in patients with GBM. Methods: A comprehensive systemic search and review was performed using the PubMed, EMBASE, and Cochrane Library databases to identify all the relevant literature (published before June 30, 2020) that evaluated the association between any of these inflammatory markers and survival in GBM. Results: There were 2 (634 patients), 3 (723 patients), 2 (237 patients), 8 (1225 patients), and 3 (505 patients) studies examining the correlation of survival with neutrophils, lymphocytes, platelets, the NLR, and the PLR, respectively. An elevated NLR and elevated neutrophil and platelet counts were associated with worse overall survival (OS) in GBM patients (NLR: hazard ratio [HR] = 1.63, 95% confidence interval [CI]: 1.23-2.15, p = 0.0007; neutrophil count: HR = 1.46, 95% CI:1.16-1.83, p = 0.001; platelet count: HR = 1.58, 95% CI: 1.42-1.77, p < 0.00001). However, there was no significant association between the PLR or the absolute lymphocyte count and OS in GBM patients. Conclusion: The NLR and the absolute neutrophil and platelet counts may be valuable and convenient peripheral inflammatory markers to evaluate the prognosis of GBM patients. Further prospective studies are needed to verify its reliability.